Color Bricks: Building Highly Organized and Strongly Absorbing Multicomponent Arrays of Terpyridyl Perylenes on Metal Oxide Surfaces. Issue 4 (3rd December 2015) - Sariola‐Leikas, Essi; Ahmed, Zafar; Vivo, Paola; Ojanperä, Anniina; Lahtonen, Kimmo; Saari, Jesse; Valden, Mika; Lemmetyinen, Helge; Efimov, Alexander
Abstract: Terpyridine‐substituted perylenes containing cyclic anhydrides in the peri position were synthesized. The anhydride group served as an anchor for assembly of the terpyridyl‐crowned chromophores as monomolecular layers on metal oxide surfaces. Further coordination with Zn 2+ ions allowed for layer‐by‐layer formation of supramolecular assemblies of perylene imides on the solid substrates. With properly selected anchor and linker molecules it was possible to build high quality structures of greater than ten successive layers by a simple and straightforward procedure. The prepared films were stable and had a broad spectral coverage and high absorbance. To demonstrate their potential use, the synthesized dyes were employed in solid‐state dye‐sensitized solar cells, and electron injection from the perylene antennas to titanium dioxide was observed. Abstract : Socket and linker : Terpyridine‐substituted perylenes containing cyclic anhydrides were assembled as monomolecular layers on metal oxide surfaces. Bis(terpyridyl) perylene diimides were used as linkers to build supramolecular assemblies by coordination with Zn 2+ ions (see figure). With proper selection of the anchor and linker highly stable, deeply colored, multilayer structures with greater than ten successive layers were prepared.